Bioprospecting of Mangrove Filamentous Fungi for the Biodegradation of Polyethylene Microplastics - Aguiar, Arthur [UNESP]; Gama, Letícia [UNESP]; Fornari, Milene [UNESP]; Neto, Almir; de Souza, Rodrigo; Perna, Rafael; Castro, Laura [UNESP]; Kovacs, Stella [UNESP]; Simões, Marta Filipa; Ferreira, Nelson; Domínguez, Yoannis [UNESP]; de Castro, Leandro [UNESP]; et al. (MDPI, 2024)
The accumulation of microplastics (MPs) in the environment has been a bottleneck for scientific society. Several approaches have been described as possibilities for reducing MPs in aquatic and terrestrial ecosystems; however, most of them are not environmentally friendly. Filamentous fungi (Ff) cells are currently considered a promising solution as a treatment for MPs. Therefore, the present study reports the potential ability of Ff isolated from mangrove sediments to biodegrade low-density polyethylene MPs (LDPEMPs). Six Ff strains were grown in batch cultures for 28 days, and one of them, Aspergillus sp. (AQ3A), showed the most prominent profile to biodegrade polymeric compounds. After morphological and molecular analysis, all strains were identified as belonging to the genera Aspergillus (MQ1C, AQ2A and AQ3A), Penicillium (MQ1A), and Trichoderma (MQ1B and MQ2A). The strain Aspergillus sp. (AQ3A) showed the most promising results with a LDPEMPs reduction rate of 47% and biomass formation of 0.0890 g·mL−1. Complementary studies with Aspergillus sp. (AQ3A) using Fourier-transform infrared spectroscopy (FTIR) highlighted changes in the molecular structure of LDPEMPs. These results indicate that Ff can contribute to the biodegradation of LDPEMPs. However, other parameters, mainly associated with the enzymes that are involved in this biodegradation process, need to be explored.
Keywords: Aspergillus; biodegradation; low-density polyethylene; mangrove filamentous fungi; microplastics